2004
DOI: 10.1111/j.1440-1827.2004.01655.x
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the p16 gene by hypermethylation and loss of heterozygosity in adenocarcinoma of the lung

Abstract: We investigated the aberrant promoter hypermethylation of p16, p15 and p14 genes and loss of heterozygosity (LOH) at 9p21-22 in 48 cases of adenocarcinoma of the lung. The frequencies of hypermethylation of genes were as follows: p16, 25.0%; p15, 22.9%; and p14, 18.8%. The frequency of LOH at chromosome 9p21-22 was 60.9%. The frequency of two-hit inactivation of the p16 gene by hypermethylation and LOH was 21.7%. Two-hit inactivation of the p16 gene showed loss of protein expression and was significantly corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…By means of a different panel of microsatellite markers detecting specific chromosome regions comprising tumor suppressor genes (FHIT, Rb, p16, p53) 1,2,8,12,28,35,36 deeply involved in lung cancer and adenocarcinoma histotype in particular. Overall, we found LOH in 55.5% of the analyzed cases then supporting the previous observations by Dacic et al 9 concerning the finding of allelic losses in SH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By means of a different panel of microsatellite markers detecting specific chromosome regions comprising tumor suppressor genes (FHIT, Rb, p16, p53) 1,2,8,12,28,35,36 deeply involved in lung cancer and adenocarcinoma histotype in particular. Overall, we found LOH in 55.5% of the analyzed cases then supporting the previous observations by Dacic et al 9 concerning the finding of allelic losses in SH.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,7,11,[17][18][19][23][24][25][29][30][31]40 Of note, EGFR mutational events seem to be quite specific of lung adenocarcinoma with BAC features. 17,18 In addition, a recent work by Dacic et al 9 suggested a common origin for SH and nm-BAC on the basis of the finding of similar patterns of allelic loss using a panel of 7 polymorphic microsatellite markers located on chromosomal regions encoding for tumor suppressor genes involved in pulmonary adenocarcinoma tumorigenesis.We report here the results of an immunohistochemical, fluorescence in situ hybridization (FISH), and polymerase chain reaction (PCR)-based molecular study by means of loss of heterozygosity (LOH) analysis using a panel of markers identifying tumor suppressor genes thought to be key molecules in the neoplastic sequential events of lung adenocarcinomagenesis (FHIT, p16, Rb, p53) 1,2,8,12,28,35,36 and also direct sequencing of EGFR (exons 18-21), HER2 (exons 19 and 20), and K-RAS …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical observations show that individuals with 9p21 LOH have better survival rates than those with homozygous deletion (16). Interestingly, experimental evidence suggests that the silencing of the remaining p16INK4A allele after allelic loss is predominantly due to epigenetic methylation rather than mutation (3).…”
Section: Loss Of Heterozygosity (Loh)mentioning
confidence: 99%
“…), biallelic inactivation through LOH combined with hypermethylation was seen in 22% of ADCs, providing a mechanism for progressive CDKN2A deregulation [145]. The p16 gene encodes cell cycle proteins (inhibitor of CDK4 and CDK6) and negatively regulates cyclin D-dependent phosphorylation of the Rb gene product, thereby inhibiting cell cycle progression from G1 to S-phase by sequestration of E2F [146,147].…”
Section: Ink4amentioning
confidence: 99%